ON THE BASIS OF XXI CONGRESS OF PEDIATRICIANS OF RUSSIA WITH INTERNATIONAL PARTICIPATION «ACTUAL PROBLEMS OF PEDIATRICS» THE RESOLUTION WAS ACCEPTED - article Editorial (Вопросы современной педиатрии)
. \